DEVELOPMENT OF TECHNOLOGY FOR ELECTROCHEMICAL INDUSTRIAL WASTEWATER TREATMENT ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The treatment of industrial wastewater has become a critical environmental and economic challenge due to the increasing volume of pollutants discharged into water bodies. Among various technologies, electrochemical methods offer significant advantages due to their efficiency, versatility, and low environmental impact. These methods, including electroflotation, electrooxidation, and electrocoagulation, have gained considerable attention as sustainable solutions for wastewater treatment in industrial sectors.